2009
DOI: 10.1111/j.1749-6632.2009.04508.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Preference for Human Social Hierarchy versus Egalitarianism

Abstract: A fundamental way that individuals differ is in the degree to which they prefer social dominance hierarchy over egalitarianism as a guiding principle of societal structure, a phenomenon known as social dominance orientation. Here we show that preference for hierarchical rather than egalitarian social relations varies as a function of neural responses within left anterior insula and anterior cingulate cortices. Our findings provide novel evidence that preference for social dominance hierarchy is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 26 publications
3
77
0
2
Order By: Relevance
“…It is notable that this subconscious social dominance / hierarchy perception paradigm elicited some similarities with our explicit forced-choice paradigm, but did not show the frontal-executive activations seen in our results. In their further study (Chiao et al, 2009b) a link between social dominance orientation (an individual's preference for a more hierarchical or egalitarian society) and empathy was made. Using a 'painful versus neutral scenario' paradigm this study (which used only female participants) reported anterior cingulate cortex activation to be correlated with social dominance orientation, independent of their dispositional empathy scores.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that this subconscious social dominance / hierarchy perception paradigm elicited some similarities with our explicit forced-choice paradigm, but did not show the frontal-executive activations seen in our results. In their further study (Chiao et al, 2009b) a link between social dominance orientation (an individual's preference for a more hierarchical or egalitarian society) and empathy was made. Using a 'painful versus neutral scenario' paradigm this study (which used only female participants) reported anterior cingulate cortex activation to be correlated with social dominance orientation, independent of their dispositional empathy scores.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that Societal and cultural factors. An examination of the influence of societal and cultural backgrounds will continue to play a large role in understanding the boundary conditions of many findings in the neuroscience of intergroup relations (e.g., Chiao, Mathur, Harada, & Lipke, 2009;Jost & Amodio, 2012;Moran et al, 2011). For example, Korean and white American participants both exhibited increased mPFC and bilateral TPJ activation when viewing same-race versus other-race targets' emotional suffering; however, Korean participants reported a significantly larger empathy gap relative to white American participants.…”
Section: How and To What Extent Do Self-representations Change In Intmentioning
confidence: 99%
“…Sidanius et al (2012) found that SDO partly determines levels of empathy and compassion. In an fMRI study, Chiao et al (2009) and Cheon et al (2011) established that SDO is strongly associated with decreased neural activity in brain regions associated with affective empathy and relative concern for others (ingroup vs. outgroup members).…”
Section: Sdo and Empathymentioning
confidence: 99%